Photoinduced electron transfer in triazole-bridged donor-acceptor dyads – A critical perspective - Müller, Carolin; Bold, Sebastian; Chavarot-Kerlidou, Murielle; Dietzek-Ivanšić, Benjamin (Coordination Chemistry Reviews, 2022)
In recent years, dyads in which molecular donor and acceptor moieties are chemically linked by a bridging ligand have emerged as attractive systems for light-driven catalysis. Their modular structure, controllable donor-acceptor distance, and their ability to undergo light-driven charge transfer, which is not limited by diffusion, render such systems promising in light-driven charge-transfer reactions and light-driven redox catalysis. Copper-catalyzed alkyne azide cycloaddition (CuAAC) is a particularly popular synthetic strategy for coupling donor and acceptor moieties. This CLICK chemistry approach yields dyads with a 1,2,3-triazole bridging motif. In this review, we discuss the complex role played by this triazole linker to drive electron transfer (eT) in a respective triazole-bridged donor-acceptor dyad upon photoexcitation. We review how structural and electronic properties of the bridge influence charge separation and recombination rates. Furthermore, the role of the triazole bridge energetics in thermal as well as oxidative and reductive photoinduced eT will be discussed. Finally, criteria for the design of dyads with different eT properties are derived.
CRIS-Team Scopus Importer:2023-11-13
Keywords: CLICK chemistry; Donor-acceptor dyads; Electron transfer; Photocatalysis; Triazole linker